PROBLEMS OF THE SETTLEMENT OF STATE LOOTED GOODS IN THE CRIMINAL ACT OF CORRUPTION AND MONEY LAUNDERING AT PT ASURANSI JIWASRAYA - Yully Lestari Tasdikin; Slamet Tri Wahyudi (International Journal Labs, 2022)
The Indonesian criminal law system has not been optimal in making the recovery of assets resulting from crimes that are not the target/focus of criminal law material because the current criminal law related to the recovery of assets resulting from crimes is only symbolic in its implementation so that the consequences for the interests of recovering the impact of crimes are regulated indirectly. and is abstract. The purpose of this study was to determine, analyze and describe the application of the authority of the Asset Recovery Center (PPA) in the settlement of state confiscations in the corruption and money laundering cases of PT Asuransi Jiwasraya (Persero). This thesis research is included in the type of normative juridical research. Normative juridical research is research in which the law is conceptualized as what is written in the legislation (law in books) or the law is conceptualized as a rule or norm which is a benchmark for human behavior that is considered appropriate. The results of the Asset Recovery Center can receive and carry out asset recovery requests from other Ministries/Agencies with the approval of the Attorney General. Therefore, the Asset Recovery Center supports the execution of state booty in the corruption and money laundering cases of PT Asuransi Jiwasraya (Persero).